Sistema para el conteo automatizado de plaquetas en muestras de sangre de pacientes de la clínica especializada Emanuel 2021 - Ramírez Sánchez, Carlos Octavio (2024)
The research was developed in the field of health, the lack of automated hematological analyzers was identified to perform platelet counting in the Health Services Provider Institutions (IPRESS) I-4 of the MINSA, as they do not have this technology that leads to manual counting, generating potential errors, delays in results and attrition of health personnel; At the Emanuel clinic this process is carried out automatically using automated hematology equipment, the results are obtained in much less time. Given this situation, it was proposed to investigate how an automated platelet counting system is effective for counting platelets in blood samples from patients at the Emanuel 2021 clinic. The objective of this study was to propose an alternative economical and efficient solution for the manual counting of platelets in blood samples, with special emphasis on the early detection of dengue. The research was quantitative, applied, quasi-experimental and descriptive. To achieve this purpose, software based on YOLO was developed, which allowed automated platelet counting. The counts performed by the software were compared with those of the automated hematology equipment revealing a p-value of 0.00 for efficacy, efficiency and effectiveness. This finding suggests that the proposed software is efficient and effective. In conclusion, this work contributes significantly to the health field by presenting an innovative and accessible, efficient and effective solution for the automated counting of platelets in blood samples.